Job satisfaction and employee performance in a public service: a case study in Ministry of Information - Abdul Rahman, Farah Adilla; Osman, Liyana (2006)
Job satisfaction is one of the evaluation aspects in work behavior, which has been emphasized by all of the organizations to guarantee the successful of the organization’s goal. In this research, the study is made at Ministry of Information due to its major responsibility to the public. Satisfaction of employees may have strong implication for the service that will be delivered to the public. Thus, for the purpose of this study, expiationary research was deployed in order to identify factors that contribute to job satisfaction. Stratified random sampling has been used with 60 respondents as the sample size. Self-administered questionnaire was used as the survey instrument as the source of primary data. Others reliable sources also served as secondary data, which were books, journal and source from internet. By using analysis generated by SPSS (computerized statistical software) results are analyzed by using frequency analysis. Finally, the finding from this study conclude that majority of employees in public service are satisfied with their job, however certain factors should be reviewed by the government such as the training and development, office equipment, office environment, job rotation, treatment from superiors and recognition to improve employees satisfaction toward their job.